Possessed by God a New Testament theology of sanctification and holiness - Peterson, David; Moore Theological College, Sydney, Aust. (Leicester, UK Apolos, 1995)
Includes bibliographical references.
Expanded from the Annual Moore Theological College Lectures, (August 1994) Sydney, Aust.
Keywords: Holiness -- Christianity -- theology